Peningkatan kapasitas kesadaran masyarakat terhadap mitigasi kerusakan pantai di Kelurahan Pelintung, Kecamatan Medang Kampai Kota Dumai-Riau - Rifardi Rifardi; Mubarak Mubarak; Dessy Yoswaty (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
Along the coast Keluruhan Pelintung has been an abrasion of 1.33-16.84 metres/year. This activity aims to increase the capacity of community awareness of coastal damage mitigation through counseling on abrasion prevention and green belt implementation techniques. The methods used were lectures, discussions, and classroom and field practice, followed by 28 community representatives. The results of the activity showed a significant increase in community's understanding of simple methods to prevent coastal damage which had a positive impact on ecology (coastal resilience) and the economy (alternative income). The method of planting mangroves on abrasive beaches is due to the influence of currents and waves and processing of mangrove fruit to produce syrup, diamonds and mangrove dodol (mangrove). The results of the economic analysis show that the pedada syrup (1 bottle @ Rp. 25,000) generates a profit of Rp. 3,192,000/month, wajik pedada (1 pack Rp. 10,000) Rp. 1,476,000/month, and dodol pedada (1 pack of Rp. 15,000) Rp. 2,760,000/month. The majority of the community stated that they supported and enthusiastically held this activity, namely 49.7% (Strongly Agree), 37.8% (Agree), 11.80% (Neutral) could accept and practice increasing community awareness of mitigating coastal damage by making mangrove planting efforts and diversification of processed mangrove products.